E.U. paediatric MOG consortium consensus: Part 4 – Outcome of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders. (November 2020) - Bruijstens, Arlette L.; Breu, Markus; Wendel, Eva-Maria; Wassmer, Evangeline; Lim, Ming; Neuteboom, Rinze F.; Wickström, Ronny; Mog consortium, E.U. paediatric; Bruijstens, Arlette L.; Wendel, Eva-Maria; Lechner, Christian; et al.
Abstract: There is increasing knowledge on the role of antibodies against myelin oligodendrocyte glycoprotein (MOG-abs) in acquired demyelinating syndromes and autoimmune encephalitis in children. Better understanding and prediction of outcome is essential to guide treatment protocol decisions. Therefore, this part of the Paediatric European Collaborative Consensus provides an oversight of existing knowledge of clinical outcome assessment in paediatric MOG-ab-associated disorders (MOGAD). The large heterogeneity in disease phenotype, disease course, treatment and follow-up protocols is a major obstacle for reliable prediction of outcome. However, the clinical phenotype of MOGAD appears to be the main determinant of outcome. Patients with a transverse myelitis phenotype in particular are at high risk of accruing neurological disability (motor and autonomic), which is frequently severe. In contrast, having a single episode of optic neuritis any time during disease course is broadly associated with a lower risk of persistent disability. Furthermore, MOG-ab-associated optic neuritis often results in good functional visual recovery, although retinal axonal loss may be severe. The field of cognitive and behavioural outcome and epilepsy following demyelinating episodes has not been extensively explored, but in recent studies acute disseminated encephalomyelitis (-like) phenotype in the young children was associated with cognitive problems and epilepsy in long-term follow-up. In conclusion, main domains of importance in determining clinical outcome in paediatric MOGAD are visual, motor, autonomic and cognitive function. A standardised evaluation of these outcome domains in all children is of importance to allow adequate rehabilitation and follow-up. Highlights: Paediatric MOGAD outcome is determined predominantly by the clinical phenotype. Functional outcome is generally good, but permanent damage is seen. Main outcome domains include visual, motor, autonomic and cognitive functions. Standardised evaluation of these outcome domains in all patients is of importance. Only then adequate rehabilitation and follow-up for the individual child is feasible.